New dimeric chromanone derivatives from the mutant strains of Penicillium oxalicum and their bioactivities. Issue 35 (10th August 2022) - Gu, Guowei; Zhang, Tao; Zhao, Jianyuan; Zhao, Wuli; Tang, Yan; Wang, Lu; Cen, Shan; Yu, Liyan; Zhang, Dewu
Abstract : Three new chromanone dimers, paecilins F–H (1–3 ) and ten known compounds (4–13 ), were obtained from the mutant strains of Penicillium oxalicum 114-2, and some of them showed significant antiviral activities. Abstract : Three new chromanone dimer derivatives, paecilins F–H (1–3 ) and ten known compounds (4–13 ), were obtained from the mutant strains of Penicillium oxalicum 114-2. Their structures were elucidated by extensive analysis of spectroscopic data and comparison with reported data, and the configurations of 1–3 were resolved by quantum chemical calculations of NMR shifts and ECD spectra. Compounds 5 and 11 showed significant anti-influenza A virus activities with IC50 values of 5.6 and 6.9 μM, respectively. Compounds 8 and 9 displayed cytotoxic activities against the MIA-PaCa-2 cell line with IC50 values of 2.6 and 2.1 μM, respectively. Compound 10 exhibited antibacterial activities against Bacillus cereus with a MIC value of 4 μg mL −1 .